Le traitement funéraire des enfants décédés avant un an dans l’Antiquité : études de cas - Frédérique Blaizot; Gersende Alix; Emmanuel Ferber (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The children who died in their first year, generally lacking or under-represented in the cemeteries, are often buried within the settlements or on their edges, or in their own cemetery. The frequent under-representation of these infants in the cemeteries is interpreted by the authors as being related to a taphonomic problem (particular physico-chemical properties of infant bones), or to differential archaeological preservation due to the shallow depth of their small graves, or to a socio-cultural choice (exclusion from the communal cemetery). We present here three funerary groups which contain a large number of children who died in their first year. One of these is a cemetery reserved for children under a year of age, another is a communal cemetery which also includes these infants, and the last can be interpreted as a space used occasionally for adults and regularly for children aged 0 to 4 years. The hypothesis of a differential preservation of the skeletons of the youngest children appears justifiable in all three examined series, in relation to the depth of the graves and to the type of burial practised. In comparison to the adults, the burials of these babies exhibit the same funerary investment in the graves (architecture, abundant and diversified objects). The groups examined here do not show a very clear difference in the treatment of the children according to whether death was perinatal or post neo-natal. Age makes no difference to the type of tomb, and although the amphoras of one site contain only children who died before 6 months, these very young children can also be found in another type of tomb. It is noted however that the children who died at birth are characterized by greater variability in the disposition of the body. The collation of the archaeological and demographic data shows that the children who died in their first year received proper funerary treatment, but this treatment varies widely according to the different groups of people. It is this great variability, in terms of topography and burial practices, that is specific to the funerary treatment of infants during Antiquity.